On a single server queue with arrivals in batches of variable size, general service in three fluctuating modes, balking, random breakdowns and a stand-by server during breakdown periods - Madan, Kailash C (Investigación operacional, 2014)
Estudiamos un sistema de colas con un solo servidor con arribos en paquetes de tamaño variable y serviciaje general en tres modos fluctuantes con diferentes tasas media de serviciaje. Se asume que justo después de completar el servicio previo o justamente después de completar la reparación o justo después de llegar un grupo nuevo de clientes en un momento en el que el sistema está en estado disponible, el servicio del próximo cliente puede comenzar en el modo j con probabilidad [p.sub.j] donde j = 1,2,3 [3.suma de (j=1)] [p.sub.j] = 1. Se asume que el sistema está sujeto a roturas aleatorias con una distribución general del tiempo de reparación. El sistema esta equipado con un servidor en espera que opera solamente durante los periodos de parada del sistema. Asumimos además que un paquete puede que arribe y deje el sistema tan pronto como llega o uede unirse al sistema. Las tasas de abandono se han sido asumidas diferentes durante los periodos de trabajo o de interrupción del servidor central. Se han obtenido resultados explícitos sobre el estado estable de la distribución del tamaño de las colas en una época aleatoria. Las probabilidades del estado libre así como el factor de utilización del sistema han sido hallados explícitamente Muchos casos particulares de interés son discutidos. We study a single server queuing system with arrivals in batches of variable size and general service in three fluctuating modes with different mean service rates. It is assumed that just after completion of the previous service or just after completion of repairs or just after arrival of a fresh batch of customers at a time when the system is in an idle state, the service to next customer may start in mode j with probability [p.sub.j] where j = 1,2,3 [3.summation over (j=1)] [p.sub.j] = 1. The system is assumed to be subject to random failures with the general repair time distribution. The system is equipped with a stand-by server which operates only during the breakdown periods of the system. We further assume that an arriving batch may balk and leave the system as soon as it arrives or may join the system. The balking rates have been assumed to be different during the working periods or the breakdown periods of the main server. Steady state results for the queue size distribution at a random epoch have been obtained explicitly. Probabilities of the idle state as well as the utilization factor of the system have been found explicitly. Many particular cases of interest are discussed. KEYWORDS: batch arrivals, balking, general service in three fluctuating modes, random breakdowns, repair times, steady state MSC: 90B22